Analisis keterampilan proses sains pada buku ajar fisika sma kelas XI semester 1 - Putri Rasti Ramadhani; Akmam Akmam; Desnita Desnita; Yenni Darvina (PILLAR OF PHYSICS EDUCATION, 2019)
Science Process Skills (KPS) are skills that facilitate learners discover facts, determine concepts and apply theories in everyday life. Textbooks are one of the learning resources that can be used. Textbooks used in high schools in West Sumatra are very diverse, and the level of KPS presentation is unknown. This study aims to determine the level of KPS presentation in Physics textbooks used by high schools in West Sumatra. This research is a descriptive study with a qualitative approach. The study population is all Physics textbooks for Class XI Semester 1 published in Indonesia and used in West Sumatra. The research sample is the four most used books in West Sumatra High School, three of which are recommended by the government. The research instrument used was very valid. Data collection technique used is the study of documents. Data analysis technique used content study. The results were obtained that the book used as a reference for learning Physics in Class XI High School Semester 1 has facilitated observational skills indicators, but has not yet facilitated the skill indicators of asking questions.